Genetic Variability and Character Association in Dolichos Bean - Magalingam, V; Yassin, Mohammed; Kumar, Ramesh (SAARC Journal of Agriculture, 2014)
Field bean (Dolichos lablab L.) is an important vegetable crop throughout India due to its local acceptability by the people. It has wide genetic variability for various traits like plant habit, branching habit, stem pigmentation, pod colour and pod characters etc. In the past, very little attention was given by the scientists on systematic crop improvement in Dolichos bean. The present investigation was laid out in a simple randomized complete block design with three replications during rabi 2011-2012 to study the variability present in 23 genotypes of dolichos bean. Analysis of variance revealed that there were significant differences among the genotypes for all the characters studied. The difference between PCV and GCV was narrow for all characters except percentage of pod set. Hence, these characters were less influenced by environment. High GCV and heritability estimates were associated with greater genetic advance for the nine traits viz., percentage of pod set, number pods per cluster, number pods per plant, green pod length, green pod width, individual green pod weight, pod yield, crude protein and crude fibre indicating that these characters had additive gene effect and were more reliable for effective selection in the improvement of dolichos bean. It is inferred from correlation and path analysis that the individual green pod weight, percentage of pod set, number of flowers per cluster and number of pods per plant exhibited significant positive correlation and direct positive effect on yield. Hence, these traits may be used as selection indices for yield improvement of dolichos bean. DOI: http://dx.doi.org/10.3329/sja.v11i2.18411 SAARC J. Agri., 11(2): 161-171 (2013)